Faculty of Pharmacy and Biochemestry of the Universidad Nacional Mayor de San Marcos, UNMSM: Origins and consolidation of pharmaceutical education in Peru - Medina, Juan Y. (2024)
The Faculty of Pharmacy and Biochemistry of the Universidad Nacional Mayor de San Marcos (UNMSM) celebrates its 80 years of institutional life. His legacy of scientific innovation and leadership training has left an indelible mark on the academic ommunity and on society, with a firm commitment to improving public health. In this commemoration, we explore the origins ofpharmaceutical education in Peru until its consolidation as a Faculty, which has been guided by the search for academic excellence and research to face challenges and contribute to scientific development in the country.